SURVEY OF FLOOD DISASTER PREPAREDNESS AMONG SCHOOL-AGE CHILDREN AT KEMIRI VILLAGE, PANTI DISTRICT, JEMBER - Latifa Aini Susumaningrum; Yerry Pristiwandono (Faculty of Nursing, Universitas Jember, 2017)
School-age children as one of population play an important role in flood natural disaster preparedness. The occurrence of flood natural disaster in Kemiri village of Panti gave both material and immaterial impacts. Flood natural disaster preparedness that can be carried out independently by the community can help empower the community independently or jointly reduce its impact. This research was a descriptive explorative research that aimed to determine the ability of school-age children about preparing themselves in the preparedness of natural flood disasters. The sample was taken by simple random sampling with 75 school age children participated in this study. Data were collected by using flood disaster preparedness questionnaire and analyzed with univariate analysis in percentage form. The results obtained that school-age children were still lacking in the 7 indicators of preparedness toward natural flash flood disaster. It was shown from each indicator that majority of children still do not have the ability toward flood natural disaster preparedness. School-age children as part of a community need to get a disaster preparedness skill that will help them take an active role in the communinity including at home and school.